Analysis of Banana Dempo Business Development in South Poleang District, Bombana Regency - Aldi Hidayat; Sarinah Sarinah; Muhammad Syukri (Jurusan Ilmu dan Teknologi Pangan, Fakultas Pertanian,, 2021)
This study aims to determine the strategy of developing a banana dempo business with a SWOT analysis in Poleang Selatan District, Bombana Regency. Determination of the research location was done purposively. Data was collected by using questionnaires, interviews, and documentation methods. The analysis used is a SWOT analysis. Based on the study results, the internal strength factor with the highest score of 0.60 is the variety and quality of the banana dempo product with a weight value of 0.15 twigs 4. The internal weakness factor with the lowest score of 0.05 is that product promotion activities are not carried out with a weight value of 0.05 branches 1. External opportunity factor with the highest score of 0.45, namely products that become typical souvenirs with a weight value of 0.15 with twigs 3. External threat factor with the lowest score of 0.15 the price of raw materials is increasing with a weight value of 0.15 twigs 1. The strategies generated in the prospect of developing the banana dempo business